1999
DOI: 10.1080/10426509908546400
|View full text |Cite
|
Sign up to set email alerts
|

Further Adventures in Germanium NMR

Abstract: The acoustic ring signal that dominates NMR spectra of low gyromagnetic ratio nuclei has always been a problem when trying to observe signals from weak samples. This work looks at some ways of improving the observability o f 7 3 G e -one such nucleus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 1 publication
4
10
0
Order By: Relevance
“…As part of our extensive investigations on the chemistry of discrete oligogermanes [13][14][15][81][82][83][84][85][86][87][88][89], we recently reported an investigation of the 73 Ge NMR spectra of several oligogermanes [13], which furthers the studies conducted by Wilkins et al [2] and Thomson et al [11]. The data from these three studies are shown in Table 9.…”
Section: Ge Nmr Spectra Of Oligogermanesmentioning
confidence: 72%
See 4 more Smart Citations
“…As part of our extensive investigations on the chemistry of discrete oligogermanes [13][14][15][81][82][83][84][85][86][87][88][89], we recently reported an investigation of the 73 Ge NMR spectra of several oligogermanes [13], which furthers the studies conducted by Wilkins et al [2] and Thomson et al [11]. The data from these three studies are shown in Table 9.…”
Section: Ge Nmr Spectra Of Oligogermanesmentioning
confidence: 72%
“…In this case, nitrogen is a stronger donor than oxygen and the ISRN Spectroscopy 7 corresponding linewidth of the germane 8 is larger than that observed for 7 which contains only oxygen atoms as potential donors. Similarly, in the triaryl-substituted germanes 9-11 (Scheme 7), the strength of the donor interaction is expected to decrease with the identity of the donor atom in the order N > O > S [53], and the order of ν 1/2 values of these compounds follows the expected trend, measuring 900 Hz (9), 350 Hz (10), and 270 Hz (11). In addition, the steric bulk of the substituent in the oxygen substituted species has little effect on the observed ν 1/2 values in these compounds, as the ν 1/2 values for 9, 12, and 13 are all 350 Hz [53].…”
Section: Spectra Of Germanesmentioning
confidence: 94%
See 3 more Smart Citations